2020
DOI: 10.34172/ajdr.2020.09
|View full text |Cite
|
Sign up to set email alerts
|

Age Estimation in Iranian Population Using Tooth/Pulp Ratio in Mandibular Premolars by Panoramic Radiography

Abstract: Background: Age estimation is a fundamental part of forensic science. Considering the fact that pulp size decreases throughout the life because of secondary dentine apposition, many researchers have used it as a method for age estimation with great results. This study aimed to determine the applicability of tooth to pulp ratio in mandibular second premolars in an Iranian population using panoramic radiographs. Methods: The sample consisted of 153 digital panoramic images of male and female Iranians aged 13-70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Estimating chronological age in adults has proven to be a much more difficult task, as confirmed in the studies retrieved in this work. None of the studies reported absolute errors lower than 2 years, and trends of under- or overestimation were also more pronounced [ 69 , 78 ]. Regarding the methods using linear or volumetric dental measurements, there is a clear improvement in terms of standard error values when volumetric information is taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimating chronological age in adults has proven to be a much more difficult task, as confirmed in the studies retrieved in this work. None of the studies reported absolute errors lower than 2 years, and trends of under- or overestimation were also more pronounced [ 69 , 78 ]. Regarding the methods using linear or volumetric dental measurements, there is a clear improvement in terms of standard error values when volumetric information is taken into account.…”
Section: Discussionmentioning
confidence: 99%
“… μ σ med. Li et al [ 67 ] PTLR (Kvaal et al) Chinese 360 20–65 + 8.6 11.80 11.40 0.23 Roh et al [ 68 ] PTLR (Kvaal et al) South Korean 266 21–69 − 9.01 11.58 12.58 7.54 10.70 0.47 Dabbaghi and Kazemi [ 69 ] PTAR (Cameriere et al) Iranian 153 13-70 + 8.83 0.52 11.06 0.54 Cameriere et al [ 70 ] PTAR (Cameriere et al) Turkish, Italian, Portuguese, Japanese and Mexican 891 20–86 2.43/2.49 Jain et al [ 159 ] TCI, PCLR Indian 180 15–70 <...…”
Section: Evaluation Studiesmentioning
confidence: 99%
See 1 more Smart Citation